1995
DOI: 10.2134/agronj1995.00021962008700060003x
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Pattern and Tillage System Effects on Corn Root and Shoot Growth

Abstract: Controlled wheel traffic is one way to manage compaction in no‐till and ridge‐till systems. This study was conducted from 1990 to 1992 at Kanawha, IA, on a Webster silty clay loam (fine‐loamy, mixed, mesic Typic Haplaquoll) to examine the effect of a wheel traffic pattern on corn (Zea mays L.) root distribution, shoot growth, and yield in no‐till, ridge‐till, and chisel‐plow tillage systems. The wheel traffic pattern was configured so that some rows would have wheel tracks on both sides, on one side, or on nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…The most important input with respect to soil carbon sequestration seems to be the plant-roots (Kong and Six, 2010). Others showed decreases in root length and biomasss in 0-0.15 m depth in wheel-tracks compared to row positions (Kaspar et al, 1991(Kaspar et al, , 1995. We reviewed the literature and found that even a small increase in soil resistance as low as 0.5 MPa by compaction would lead to a decrease in root length and biomass (Barzegar et al, 2006;Bingham et al, 2010).…”
Section: Higher Carbon Inputs Under the Wheel-track?mentioning
confidence: 92%
“…The most important input with respect to soil carbon sequestration seems to be the plant-roots (Kong and Six, 2010). Others showed decreases in root length and biomasss in 0-0.15 m depth in wheel-tracks compared to row positions (Kaspar et al, 1991(Kaspar et al, , 1995. We reviewed the literature and found that even a small increase in soil resistance as low as 0.5 MPa by compaction would lead to a decrease in root length and biomass (Barzegar et al, 2006;Bingham et al, 2010).…”
Section: Higher Carbon Inputs Under the Wheel-track?mentioning
confidence: 92%
“…Care was also taken to sample in similar row positions on all plots and to avoid wheel tracks, but it is still possible that some less obvious wheel tracks were sampled, adding variability and making it very difficult to detect smaller changes due to the cover crop. Kaspar et al (1995) found that trafficked interrows had up to a 36% higher bulk density [84 lb ft ]) averaged across different tillage systems including chisel plow and no till, highlighting the need to plan sampling locations carefully.…”
Section: Depth (Cm)mentioning
confidence: 99%
“…A densidade é negativamente relacionada com a porosidade de aeração e positivamente relacionada com a resistência do solo à penetração das raízes (Archer & Smith, 1972;Ehlers et al, 1983;Silva et al, 1994). Os efeitos dos sistemas de preparo na variação da densidade do solo podem ser manifestados de forma diferenciada de acordo com a intensidade de tráfego e a posição relativa à linha de semeadura (Kaspar et al, 1991;Kaspar et al, 1995). No entanto, há carência de trabalhos que abordem este tema (Cassel, 1982;Kaspar et al, 1995;Silva et al, 1997).…”
Section: Introductionunclassified
“…Os efeitos dos sistemas de preparo na variação da densidade do solo podem ser manifestados de forma diferenciada de acordo com a intensidade de tráfego e a posição relativa à linha de semeadura (Kaspar et al, 1991;Kaspar et al, 1995). No entanto, há carência de trabalhos que abordem este tema (Cassel, 1982;Kaspar et al, 1995;Silva et al, 1997).…”
Section: Introductionunclassified